Prosedur Pemeriksaan MRI Placenta Accreta Di RSUD Dr Saiful Anwar Malang - Stefania Layola Pasire; I Putu Eka Juliantara; I Wayan Ariec Sugiantara (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Placenta accreta is an abnormal implantation of the placenta into the uterine wall, on the surface of the myometrium. Placenta accreta is quite dangerous for pregnancy and has increased over the past few years along with the incidence of cesarean section (SC), with a prevalence of 7-10% of maternal deaths in the world. To diagnose the incidence of placenta accreta, Magnetic Resonance Imaging (MRI) is one of the modalities that is often utilized and has now become a routine diagnostic support modality in many large hospitals, because it does not use ionizing radiation and has a higher contrast resolution. The type of research used is qualitative with a case study approach. The sample of this study consists of 2 patients who underwent MRI Abdomen-Pelvic with clinical placenta accreta at RSUD Dr. Saiful Anwar Malang, which was conducted during September 2023. The results of this study indicate that the placenta accreta MRI examination procedure at RSUD Dr. Saiful Anwar Malang has no special preparation. The use of 2 protocols in the examination, namely abdomen and pelvic, has the advantage of producing a wider cross section, also including several additional sequences in the form of DWI and MRA, thus helping to observe the area of adhesions and surrounding organs, with the boundaries of the organs produced much more clearly.